2016
DOI: 10.5127/pr.037214
|View full text |Cite
|
Sign up to set email alerts
|

Information Processing in PTSD: Evidence for Biased Attentional, Interpretation, and Memory Processes

Abstract: This comprehensive review surveys current literature on information processing biases in posttraumatic stress disorder (PTSD). The review is organized by information processing systems including attention, judgment and interpretation, and memory. Studies outlined suggest that information processing biases may be key factors involved in the development and maintenance of PTSD. However, inconsistencies exist in the literature within each domain, often depending on assessment paradigm employed or other methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 114 publications
(182 reference statements)
2
43
0
2
Order By: Relevance
“…Post-traumatic stress disorder (PTSD) is a disorder that may occur after the experience of a traumatic, life-threatening event (e.g., physical or sexual assault, combat, or natural disasters). Researchers attribute the core features of PTSD (avoidance, negative alterations in cognition and mood, re-experiencing, and alterations in arousal and reactivity; American Psychiatric Association, 2013) to a number of disturbed dysfunctional cognitive systems, such as altered attention, perception, memory, and judgment (Johnson, Bomyea, & Lang, 2016). The presumed importance is also reflected by popular theoretical models of PTSD, which include distinct cognitive processing as a fundamental part of development and maintenance of PTSD (Brewin, Dalgleish, & Joseph, 1996;Ehlers & Clark, 2000;Foa, Steketee, & Rothbaum, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Post-traumatic stress disorder (PTSD) is a disorder that may occur after the experience of a traumatic, life-threatening event (e.g., physical or sexual assault, combat, or natural disasters). Researchers attribute the core features of PTSD (avoidance, negative alterations in cognition and mood, re-experiencing, and alterations in arousal and reactivity; American Psychiatric Association, 2013) to a number of disturbed dysfunctional cognitive systems, such as altered attention, perception, memory, and judgment (Johnson, Bomyea, & Lang, 2016). The presumed importance is also reflected by popular theoretical models of PTSD, which include distinct cognitive processing as a fundamental part of development and maintenance of PTSD (Brewin, Dalgleish, & Joseph, 1996;Ehlers & Clark, 2000;Foa, Steketee, & Rothbaum, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…geht die Entwicklung einer PTBS nach einem traumatischen Ereignis v. a. auf dysfunktionale kognitive Prozesse zurück. Dies können automatische Voreinstellungen ("cognitive bias") bei Prozessen der Aufmerksamkeit, Interpretation und bei Gedächtnisphänomenen sein [42]. Automatisch ablaufende dysfunktionale Einschätzungen bzw.…”
Section: Veränderung Automatischer Dysfunktionaler Kognitionenunclassified
“…Attentional biases towards trauma-related information are commonly seen in PTSD (McNally, Kaspi, Riemann, & Zeitlin, 1990;Bryant, Harvey, Gordon, & Barry, 1995), although some studies have shown an absence of such biases (for review, see Hayes, VanElzakker, & Shin, 2012;Bomyea et al, 2017). Studies investigating selective attention such as the dot-probe paradigm have shown biases towards (Bryant & Harvey, 1997;Dalgleish, Moradi, Taghavi, Neshat-Doost, & Yule, 2001;Dalgleish et al, 2003;Fani et al, 2012) and away from (Pine et al, 2005;Fani, Bradley-Davino, Ressler, & McClure-Tone, 2011) trauma-related or other negative ATTENTION AND MEMORY BIASES IN PTSD stimuli in PTSD, while other studies have shown no bias (Badura-Brack et al, 2015;Iacoviello et al, 2014).…”
Section: Introductionmentioning
confidence: 99%